2014
DOI: 10.1089/ten.tea.2013.0672
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Gene Expression in the Retina by Improved Episomal Vectors

Abstract: Gene and cellular therapies are nowadays part of therapeutic strategies for the treatment of diverse pathologies. The drawbacks associated with gene therapy-low levels of transgene expression, vector loss during mitosis, and gene silencing-need to be addressed. The pEPI-1 and pEPito family of vectors was developed to overcome these limitations. It contains a scaffold/matrix attachment region, which anchors its replication to cell division in eukaryotic cells while in an extrachromosomal state and is less prone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 23 publications
1
20
0
Order By: Relevance
“…The NGF concentration was significantly increased in pEGFP-C1-MAR-NGF, compared to that of CHO cells transfected with pEGFP-C1-NGF. These results are in agreement with those of a previous study (Calado et al, 2014). RT-PCR analysis indicated a significantly increased target NGF mRNA expression in CHO cells transfected with pEGFP-C1-MAR-NGF, compared to that in CHO cells transfected with the pEGFP-C1-NGF or pEGFP-C1 vectors.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The NGF concentration was significantly increased in pEGFP-C1-MAR-NGF, compared to that of CHO cells transfected with pEGFP-C1-NGF. These results are in agreement with those of a previous study (Calado et al, 2014). RT-PCR analysis indicated a significantly increased target NGF mRNA expression in CHO cells transfected with pEGFP-C1-MAR-NGF, compared to that in CHO cells transfected with the pEGFP-C1-NGF or pEGFP-C1 vectors.…”
Section: Discussionsupporting
confidence: 93%
“…MAR contains some characteristic sequence components, including a T-box (TTTTATTTTT), an A-box (AATAAAAA/CAA), an autonomous replicating DNA sequence, and fruit fly topoisomerase II recognition sites (Ehrhardt et al, 2008;Mucller and Flotte, 2008). The MAR also mediates the attachment of vectors to host cells (Chiaretti et al, 2008;Zheng et al, 2010;Calado et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…For example, a newer version of pEPI was constructed with a CpG-depleted backbone, called pEPito (171). Experiments have shown that pEPito can drive stable transgene expression at higher levels and for a longer time period than its successor pEPI in vitro and in vivo especially in the retina (171, 172). This has the added benefit of a minimized inflammatory response (173), which is often associated with typical CpG patterns in bacterial backbones (174).…”
Section: Vector Engineeringmentioning
confidence: 99%
“…Inclusion of this enhancer can be used to improve the expression of normally weak but tissue-specific promoters without compromising the specificity of the promoter (198), and has been implemented in the eye with the RPE65 promoter (172). This enhancer effect has also been demonstrated for regions from other promoters such as the photoreceptor-specific interphotoreceptor retinoid binding protein (IRBP), even though the effect is much less potent than in the case of CMV (65).…”
Section: Vector Engineeringmentioning
confidence: 99%
“…The first nonviral and episomal plasmid vector pEPI based on the matrix attachment region (MAR), which can replicate autonomously with low copy numbers in all cells tested, was developed by Piechaczek et al [7]. However, the pEPI vector has several limitations, such as low copy number, unstable expression and low expression level [8,9].…”
Section: Introductionmentioning
confidence: 99%